A modified Mediterranean diet score is associated with a lower risk of incident metabolic syndrome over 25 years among young adults: the CARDIA (Coronary Artery Risk Development in Young Adults) study. Issue 10 (28th November 2014) - Steffen, Lyn M.; Van Horn, Linda; Daviglus, Martha L.; Zhou, Xia; Reis, Jared P.; Loria, Catherine M.; Jacobs, David R.; Duffey, Kiyah J.
<x content-type="archive" xml:space="preserve">Abstract</x> The Mediterranean diet has been reported to be inversely associated with incident metabolic syndrome (MetSyn) among older adults; however, this association has not been studied in young African American and white adults. The objective of the present study was to evaluate the association of a modified Mediterranean diet (mMedDiet) score with the 25-year incidence of the MetSyn in 4713 African American and white adults enrolled in the Coronary Artery Risk Development in Young Adults (CARDIA) study. A diet history questionnaire was used to assess dietary intake at baseline, year 7 and year 20 and a mMedDiet score was created. Cardiovascular risk factors were measured at multiple examinations over 25 years. The MetSyn was defined according to the National Cholesterol Education Program Adult Treatment Panel III (ATP III) criteria. Cox proportional-hazards regression analysis was use to evaluate associations for incident MetSyn across the mMedDiet score categories adjusting for demographic characteristics, lifestyle factors and BMI. Higher mMedDiet scores represented adherence to a dietary pattern rich in fruit, vegetables, whole grains, nuts and fish, but poor in red and processed meat and snack foods. The incidence of MetSyn components (abdominal obesity, elevated TAG concentrations and low HDL-cholesterol concentrations) was lower in those with higher mMedDiet scores than in those with lower scores. Furthermore, the incidence of the MetSyn was lower across the five mMedDiet score categories; the hazard ratios and 95 % CI from category 1 to category 5 were 1·0; 0·94 (0·76, 1·15); 0·84 (0·68, 1·04); 0·73 (0·58, 0·92); and 0·72 (0·54, 0·96), respectively (Ptrend= 0·005). These findings suggest that the risk of developing the MetSyn is lower when consuming a diet rich in fruit, vegetables, whole grains, nuts and fish.